(untitled) (Orfeu, 2023)
This article describes the discovery of a collection of piano manuscripts by composer Lydia do Amaral (1855?-1948), which remained in almost total oblivion until 2017, when they were found by family members inside a trunk at one of the family’s farms, close to Capivari (SP). To better understand the value of her works, the article has the following objectives: (1) to conduct a brief biographical survey of the composer, based on interviews with her family members and on a few bibliographical sources that mention her; (2) to situate her pieces within their historical context, also considering the situation and the limits imposed by society on a woman composer in Brazil at that time; (3) to present analyses and descriptions of excerpts from three representative works from the collection. As a result, the article demonstrates the high compositional quality and artistic refinement of Lydia do Amaral’s oeuvre, encouraging other pianists and researchers to explore this collection.